Sistem Informasi Desa Kiringan Berbasis Website Menuju Desa Cerdas Menggunakan Metode Prototype - Muhamad Dani Prasetya; Fariyono Fariyono; Donna Setiawati (Universitas Boyolali, 2022)
Kiringan Boyolali Village in implementing a website-based information system is still not optimal, so that people still have difficulty in finding information about the village via the internet. Previously, the Kiringan Boyolali Village Website already existed but the features displayed were incomplete, namely only village profiles, village demographics, photo galleries, and contacts. As an initial step in developing Smart Villages in the field of information technology, it is necessary to develop a website in Boyolali Kiringan Village, by adding various features, namely the homepage menu, village profiles, news, village data, village institutions, village potential, and complaints, with the aim of helping the village government Kiran in managing and developing village websites. The development of the website uses the Prototype method with the results of updating a website-based information system in Kiringan Boyolali Village. This system has been tested using beta testing based on a media questionnaire to users. The test results show that the function on this website as a whole has been running well.